Application of fuzzy VIKOR method for the evaluation and selection of a suitable tugboat. (May 2020) - Balin, Abit; Şener, Bekir; Demirel, Hakan
Tugboats have a very critical role in numerous fields of the maritime sector. There are many types of tugboats with different characteristics that give superior results in different operations. Choosing the most suitable tugboat type for the desired operation is a multi-criteria problem that requires expertise. The design features of the tugboat and the propulsion system are important features used for classification. In addition, operational, environmental, and financial factors are also of considerable importance. In this article, determined criteria for tugboats classified according to their propulsion systems have been evaluated by subject-matter experts through a questionnaire. Fuzzy Shannon Entropy has been used to calculate the weights of each determined criterion. Then, fuzzy VIKOR was selected to rank the alternatives due to good compatibility with Entropy and the ability to adequately distinguish the table values that compose the ranking. Finally, the most suitable tugboat type was chosen in accordance with these results.